QUALITY OF LIFE IN PATIENTS AFTER ACUTE CORONARY SYNDROME IN A LIFESTYLE CONTEXT - Šulcová, J.; Murgová, A. (Україна. Здоров’я нації, 2023)
Acute coronary syndrome belongs to the diseases that are the result of a combination of several risk factors, which can be uncontrollable or controllable. Everyone takes charge of the factors which can be affected by preventive activities. Most of the risk factors are associated with the so-called modern lifestyle; therefore, ACS is classified as a disease of civilization. Health should be the number one priority for the individual, family, and society. It is also a prerequisite for an active life. Moreover, it affects our daily activities, which we perform either at work as duties or in our personal lives. It is influenced by many factors, such as lifestyle, health, and preventive behaviour of the patient, quality of life, or interpersonal relationships. In health care, health promotion and disease prevention have become important elements, which include efforts to improve overall health. The most important factors in health care are not the financial resources, technical and material equipment of health services, but individuals themselves; their way of thinking, living and willingness to participate effectively in their health care, to show will and perseverance, be intolerant to own laziness, arm themselves with knowledge and seek the way to health because as the old Eastern saying says: “Who does nothing, does not satisfy his own needs”.